Characteristics that modify the effect of small-quantity lipid-based nutrient supplementation on child growth: An individual participant data meta-analysis of randomized controlled trials - Dewey, Kathryn G.; Wessells, K. Ryan; Arnold, Charles D.; Prado, Elizabeth L.; Abbeddou, Souheila; Becquey, Elodie; Huybregts, Lieven; Leroy, Jef L.; Ruel, Marie T. (American Society for Nutrition, 2021)
Background: Meta-analyses show that small-quantity lipid-based nutrient supplements (SQ-LNSs) reduce child stunting and wasting. Identification of subgroups who benefit most from SQ-LNSs may facilitate program design. Objectives: We aimed to identify study-level and individual-level modifiers of the effect of SQ-LNSs on child growth outcomes. Methods: We conducted a 2-stage meta-analysis of individual participant data from 14 randomized controlled trials of SQ-LNSs provided to children 6–24 mo of age (n = 37,066). We generated study-specific and subgroup estimates of SQ-LNS compared with control and pooled the estimates using fixed-effects models. We used random-effects meta-regression to examine study-level effect modifiers. In sensitivity analyses, we examined whether results differed depending on study arm inclusion criteria and types of comparisons. Results: SQ-LNS provision decreased stunting (length-for-age z score < −2) by 12% (relative reduction), wasting [weight-for-length (WLZ) z score < −2] by 14%, low midupper arm circumference (MUAC) (<125 mm or MUAC-for-age z score < −2) by 18%, acute malnutrition (WLZ < −2 or MUAC < 125 mm) by 14%, underweight (weight-for-age z score < −2) by 13%, and small head size (head circumference-for-age z score < −2) by 9%. Effects of SQ-LNSs generally did not differ by study-level characteristics including region, stunting burden, malaria prevalence, sanitation, water quality, duration of supplementation, frequency of contact, or average compliance with SQ-LNS. Effects of SQ-LNSs on stunting, wasting, low MUAC, and small head size were greater among girls than among boys; effects on stunting, underweight, and low MUAC were greater among later-born (than among firstborn) children; and effects on wasting and acute malnutrition were greater among children in households with improved (as opposed to unimproved) sanitation. Conclusions: The positive impact of SQ-LNSs on growth is apparent across a variety of study-level contexts. Policy-makers and program planners should consider including SQ-LNSs in packages of interventions to prevent both stunting and wasting. This trial was registered at www.crd.york.ac.uk/PROSPERO as CRD42019146592.